Doenças ortopédicas de etiologia traumática do sistema locomotor de cães: 1.200 casos (2004-2013) - Libardoni, Renato do Nascimento (2015)
The objective of this study was to identify and determine the prevalence of fractures and traumatic appendicular luxations in dogs treated between January 2004 and December 2013 at the Hospital Veterinário Universitário da Universidade Federal de Santa Maria. In a population of 1200 dogs with suspected traumatic orthopedic diseases in the locomotor system, 955 (79.58%) had appendicular fractures and 245 (20.42%) had appendicular luxations. Of the 955 dog with fractures, 23.56% had fractures of the femur (n = 225), 23.36% pelvic fractures (n = 223), 21.99% tibial and fibula fractures (n = 210), 17.58% radius and ulna fractures (n = 168), 7.54% humerus fractures (n = 72) and 5.97% distal fractures to the tarsus and carpus (n = 57), with the most frequent cause by car accidents (72.21%). The most affected dogs with fractures were male (52.46%), young (41.99%), mixed breed (51.41%) and small size (42.7%). Of the 245 dogs (20.42%) with traumatic luxations, 57.14% were composed by hip luxations (n = 140), patellar luxation 15.1% (n = 37), 9.8% elbow luxations (n = 24), 5.71% sacroiliac luxations (n = 14), 4.49% shoulder luxations (n = 11) and 7.76% of dogs had other luxations (n = 19), with the most frequent cause by car trauma (66.12%). The most affected dogs with traumatic luxations were males (50.2%), mature adults (36.73%), mixed breed (43.67%) and small size (50.48%). In conclusion, in the population of dogs evaluated, the most prevalent appendicular fractures were femoral fractures, pelvic fractures, fractures of the tibia and the fibula and radius and ulna fractures; and the most prevalent traumatic appendicular luxations were hip luxations, patellar luxations and elbow luxations.